2016
DOI: 10.17268/sci.agropecu.2016.02.07
|View full text |Cite
|
Sign up to set email alerts
|

The ultrasound technology for modifying enzyme activity

Abstract: Enzymes are protein complexes compounds widely studied and used due to their ability to catalyze reactions. The food processing mainly aims the inactivation of enzymes due to various undesirable effects. However, there are many processes that can be optimized by its catalytic activity. In this context, different technologies have been applied both to inactivate or to improve the enzymes efficiency. The Ultrasound technology emerges as an alternative mainly applied to achieve the enzyme inactivation. On the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…The outcome from this study is consistent with Rojas, Hellmeister Trevilin, Augusto, and Esteves (2016), who studied the effect of ultrasound cavitation on POD, and reported that the activity of POD declined as a result of conformational changes upon sonolysis.…”
Section: Effect Of Different Pretreatment Methods On the Percentagesupporting
confidence: 90%
“…The outcome from this study is consistent with Rojas, Hellmeister Trevilin, Augusto, and Esteves (2016), who studied the effect of ultrasound cavitation on POD, and reported that the activity of POD declined as a result of conformational changes upon sonolysis.…”
Section: Effect Of Different Pretreatment Methods On the Percentagesupporting
confidence: 90%
“…However, no studies are available for the activation of linamarase by ultrasonic treatment. Contrarily, a decrease in enzymes activity by ultrasound has been observed (Islam, Zhang, & Adhikari, 2014;Lindsay Rojas, Hellmeister Trevilin, & Augusto, 2016). Hence, ultrasonic treatment effects may differ with the intensity and frequency, type of enzyme, and inhibiting or activating factors (Kwiatkowska et al, 2011).…”
Section: Toxicology and Chemical Food Safetymentioning
confidence: 99%
“…In addition, the authors observed that the US increased products formation when combined with lower temperatures (40-60°C), indicating that the effect of ultrasound on the AMG is dependent of the equipment type, the conditions applied and the form applied (only in the enzymatic solution or in the reactions carried out under ultrasound). In fact, even the same amount of added ultrasonic energy, though considering different systems, can result in opposite behaviour (Rojas, Trevilin, & Augusto, 2016), due to differences on the acoustic field distribution.…”
Section: Effect Of Ultrasonic Processing On Enzyme Activitymentioning
confidence: 99%